STRATEGI DAKWAH DALAM MELESTARIKAN NILAI-NILAI DAKWAH PADA TRADISI MAPPACCING DI DESA BALONG KECAMATAN UJUNGLOE KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The results showed that the Da'wah Strategy in Preserving Da'wah Values in the Mappaccing Tradition in Balong Village, Ujungloe District, Bulukumba Regency, namely the first oral dakwah strategy, namely the delivery of da'wah messages concerning mappaccing so that the da'wah still provides maximum function for the benefit of life. The two strategies of takziyah are by instilling Islamic values, namely cleanliness and purity. The third is da'wah which provides an example and maintains the tradition of mappaccing in one's own family so that it can be carried out by future descendants. And the procession of the mappaccing tradition in Balong Village, Ujungloe District, Bulukumba Regency, namely the first Barasanji reading, which is carried out at the beginning of the activity with the hope of increasing faith and love for the Prophet Muhammad. The two Mappenre Temme (khatam Al-Qur'an), namely the reading of the holy verses of the Koran which are very thick with Islamic values, have da'wah values, namely as motivation to children, human relations with Allah SWT, increasing gratitude and strengthening the rope hospitality.